Trauma Of Violence In The Brief Wondrous Life Of Oscar Wao; A Psychological Analysis - Amelia Yuli Astuti; Situasi Putra Jaya Laia Situasi Putra Jaya Laia (Jurnal Ilmiah Pendidikan Scholastic, 2026)
This reseach examines the "Trauma of violence in The Brief Wondrous Life of Oscar Wao by Junot Díaz. Through Psychological analysis using the theory of Archetypes, shadow, and Collective unconcious developed by Carl Jung. With a qualitative text analysis approach, the researcher wants to explore how the violent experiences of the characters in the novel, especially Oscar Wao and his family, affect the deep psychological impact. The main focus of the reseach was on identifying the violence experienced by the characters, how individuals reacted to the shadows and how the history of family trauma experiences affected emotional actions and relationships within the family. The findings show that the violence experienced by the characters not only affects their personal lives, but also reflects broader collective trauma in the context of Dominican history and culture under the rule of Rafael Trujillo's regime. This research contributes to the understanding of how literature can reflect and reveal complex psychological experiences towards the development of characters' emotional actions in living their lives.